Dezentrale Besiedlung als Herausforderung für die Raumentwicklung. Eine Fallstudie der Region Surselva in Graubünden. - (:unkn) unknown (TH Zürich, NSL, 2008)
Die Fallstudie in der Region Surselva wurde im interdisziplinären Forschungsprojekt "Dezentrale Besiedlung - Erfolgs- oder Auslaufmodell" mit Beteiligten aus den Disziplinen Regionalökonomie, Politologie, technische Infrastruktur und Raumentwicklung sowie Ökologie bearbeitet. Als Untersuchungsregion wurde die MS (=mobilité spatiale)-Region Surselva ausgewählt, eine Region im Alpenraum, deren Status als peripherer ländlicher Raum unbestritten ist. Im Beitrag wird die Surselva zunächst hinsichtlich Siedlungsstruktur und demographischer Entwicklung als dezentral besiedelte Region porträtiert. Anschließend werden die ökonomischen Herausforderungen, die Funktionsfähigkeit des Gemeindesystems und die aktuelle Situation der Ver- und Entsorgung dargestellt. Zum Abschluss werden Landschaftsmodellierungen präsentiert, die mögliche ökologische Auswirkungen einer Aufgabe dezentraler Siedlungsstrukturen aufzeigen.

The article presents an interdisciplinary analysis of the issues of decentralized settlement by focusing, on the challenges faced in this realm by the region of Surselva in the Canton of Grisons. More precisely, we analyze the economic, institutional, infrastructural and ecological implications of recent socio-economic changes in this region, showing that the current pressure on decentralized settlements is a multi-dimensional phenomenon. The analysis draws on data stemming from qualitative interviews, secondary socio-economic and survey data, as well as ecological modelling. Overall, the results show that there is not a uniformity of pressures on decentralized settlements in the Surselva region. At the economic level, the situation is one of a patchwork, polarized regional development, where areas of decline co-exist with pockets of dynamic growth. At the institutional level, municipalities in the declining areas have come under strong pressure to amalgamate, in spite of local resistance. The effect is looming political catharsis in these areas. Concerning infrastructure, the general problem is inefficiency due to oversize capacities, either because of shrinking demand (in declining areas) or high seasonal fluctuation of demand (in growth areas). Finally, ecological modelling shows that the eventual extension of land use would lead to a loss of biodiversity resulting in a significant change of the landscape. In the conclusion, the implications of these findings for Swiss regional policy are discussed more generally.
Decentralized settlement as a challenge for spatial development: A case study of the Surselva region in Graubünden.
Keywords: Siedlungsstruktur; Ländlicher Raum; Raumplanung; Technische Infrastruktur; Regionalwirtschaft; Landschaftsökologie; Regionalentwicklung; Bevölkerungsentwicklung; Fallstudie; Dezentralität; Peripherie; Periphere Region; Demographische Entwicklung